Pulsed cyclophosphamide, thalidomide and dexamethasone regimen for previously treated patients with multiple myeloma: Long term follow up and disease control after subsequent treatments - Roussou, M.; Anagnostopoulos, A.; Kastritis, E.; Matsouka, C.; Barmparousi, D.; Koutsoukou, V.; Dimopoulos, M.A. (Leukemia and Lymphoma, 2007)
There are limited data regarding the long term follow up after thalidomide based regimen and the outcome of patients when they progress and they receive further treatment. We reassessed our original series of 43 patients with previously treated multiple myeloma who had received a pulsed cyclophosphamide, thalidomide, dexamethasone (CTD) regimen. Among the 43 patients, 14 did not respond to pulsed CTD and 29 (67%) achieved at least a partial response. The median PFS for all patients was 10 months. After a median follow up of 24 months (range 1-62), the 3 year PFS is 14% and 3 patients remain off treatment and without progression for 55+, 55+ and 56+ months respectively. Moreover, 28% of patients who progressed after CTD achieved a partial response after subsequent treatment which included thalidomide, bortezomib or lenalidomide. The median PFS of these patients was 5 months and the 1 year PFS was 20%. Furthermore, 31% of patients who had responded to CTD and then progressed (CTD sensitive) responded to subsequent treatment. We conclude that some patients enjoy long responses after CTD and that several patients who progress after CTD may respond to treatment with a novel agent-based regimen.
Keywords: Long term follow up; multiple myeloma; novel agents; Thalidomide